A City of Two Tales: Shelter and Migrants in Surabaya. (March 2017) - Das, Ashok
This paper describes shelter and related deprivations that poor migrants to Surabaya, Indonesia, endure. Surabaya is renowned as the pioneer of the Kampung Improvement Program (KIP)—a type of citywide slum upgrading, an effective pro-poor shelter intervention. Although Surabaya has ostensibly embraced inclusive planning and governance, this paper argues it still unjustly burdens poor migrants with policies that are exclusionary and iniquitous. Qualitative evidence from a decade of field research in Surabaya points out that shelter accessibility discriminates between its eligible and ineligible poor, that is, the city's so-called citizens and outsiders. It posits that Surabaya's contemporary shelter interventions comprises two phases, KIP and post-KIP. Extensive settlement upgrading marked the pre-decentralization KIP-phase. After decentralization in 1999, the post-KIP phase saw the city prioritize rental flats for the poor. Curiously, it is because of the KIP-phase, which did not address housing per se, that Surabaya's migrants still find affordable shelter. The post-KIP phase has done little to alleviate the shelter woes of the city's poor migrants despite their demonstrated potential to produce sustainable and inclusive alternatives. The analysis suggests that political will and civil society participation can alter the shelter status quo of Surabaya's migrant poor.